1993
DOI: 10.1023/a:1018936806278
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To evaluate the usefulness of liposomes as a carrier for the targeted delivery of antigens to gut-associated lymphoid tissue, liposomal stability and uptake by rat Peyer's patches were investigated. Liposomes composed of distearoylphosphatidylcholine, phosphatidylserine, and cholesterol (DSPC-liposome), or dipalmitoylphosphatidylcholine, phosphatidylserine, and cholesterol were stable in acidic solution (pH 2.0), diluted bile, and pancreatin solution. Following the oral administration of liposomes to rats, rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Regarding liposome size, Aramaki et al reported that multilamellar liposomes (MLV) larger than 374 nm in size were taken up through rat Peyer's patches after oral administration using isolated tissues. 28 The MLV liposomes have been used in many cases for oral administration, [11][12][13][14][15] while REV liposomes have not.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding liposome size, Aramaki et al reported that multilamellar liposomes (MLV) larger than 374 nm in size were taken up through rat Peyer's patches after oral administration using isolated tissues. 28 The MLV liposomes have been used in many cases for oral administration, [11][12][13][14][15] while REV liposomes have not.…”
Section: Discussionmentioning
confidence: 99%
“…Peyer's patches are an important absorption pathway for antigenic or lipophilic drugs as this route can be used for targeting (Aramaki et al, 1993). Peyer's patches are an important absorption pathway for antigenic or lipophilic drugs as this route can be used for targeting (Aramaki et al, 1993).…”
Section: Animal Experimentsmentioning
confidence: 99%
“…The formulations are designed for oral administrations. Peyer's patches are an important absorption pathway for antigenic or lipophilic drugs as this route can be used for targeting (Aramaki et al, 1993). In this and previous studies, the immunological properties of lipids in liposomes and nanocochleates were utilized (De Libero, Collmann, & Mori, 2009).…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Cell targeting studies have been investigated and produced significant data and observations of how antigen presentation plays a significant role. Aramaki et al investigated the utilization of liposomes as carriers for antigens related to gut-associated lymphoid tissue and their uptake by rat Peyer’s patches [ 63 ]. Preferential uptake was observed for liposomes in the rat Peyer’s patches than non-patch tissues, specifically for DSPC:PS:Chol liposomes.…”
Section: Liposome-immune Cell Interactions To Improve Vaccine Effectimentioning
confidence: 99%